METAMORPOSER: REPRESENTASI VISUAL KEHIDUPAN DALAM MEDIA TEMBUS PANDANG - Luna Dian Setya (Jurnal Bahasa Rupa, 2019)
Butterflies are God's creatures that are considered beautiful and the final form of a changing process called metamorphosis. Humans and butterflies undergone phase of changes to reach maturity, both also have similar behaviors to maintain their existence. Relics from the beginning of the history show that humans in various parts of the world have observed the life of butterflies and depicted them in works of art. This final project of art creation took butterflies as a representation of life that experiences conflict between internal urgency and the desire to meet the external demand, this process is seen as the path to self totality. Butterfly as a metaphor not only appear in the picture; their characteristics also showed in the artwork. The characteristics of butterfly wings that can be seen from two sides, lightweight and thin presented in the artwork through the use of tracing paper as medium.